2020
DOI: 10.6000/1929-4247.2020.09.04.7
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Acceptable Diet and its Predictors among Children Aged 6-23 Months in Mareka District, Southern Ethiopia: Community Based Cross-Sectional Study

Abstract: Background: Optimal infant and young child feeding practices are essential for normal growth, better health, and mental and physical development. Even though there are a lot of nutrition intervention programs in Ethiopia, still suboptimal feeding practices are prevalent. This study was devised to assess a level of minimum acceptable diet (MAD) and predictors among children aged 6-23 months in Mareka District, south Ethiopia. Method: A community-based cross-sectional study was employed on 662 study participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 26 publications
7
21
1
Order By: Relevance
“…The current study found that as the age of children increases, the odds of having inadequate minimum DD decreases, which implies that the practice of adequate minimum DD significantly increases as the child's age increases. This is similar to studies conducted in Indonesia (9), Bangladesh (47), Malawi (16), and Ethiopia (14,28).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The current study found that as the age of children increases, the odds of having inadequate minimum DD decreases, which implies that the practice of adequate minimum DD significantly increases as the child's age increases. This is similar to studies conducted in Indonesia (9), Bangladesh (47), Malawi (16), and Ethiopia (14,28).…”
Section: Discussionsupporting
confidence: 89%
“…Children from lower-middle and higher middle-income level countries also have less chance to have inadequate MDD as compared to lower-income levels. This is in line with a study conducted in India (27,61,62), Bangladesh (47), South Asia (22), Tanzania (25), and Ethiopia (12,55,56), but other studies in Ethiopia showed that no association with it (10,14). This difference might be due to the small sample size and covers the small district of the latter two studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As a result, the source of heterogeneity was deference towards residence (Table 2). and child age [43][44][45], ANC [21,22], PNC [21,24,25,28,46], Household food insecurity [42][43][44], maternal education [25,42,47], wealth index [22,25,28,43,45,46], nutrition information [27,28,43], mothers' decision power [26,27], media exposure [23,25,27,45,48], maternal knowledge [26,49] and residence [17,28,50]) had data that could be used in the quantitative meta-analysis. Greater heterogeneity was observed among studies evaluating maternal decision-making, the age of the child, and being both middle and rich wealth groups (Table 3).…”
Section: Meta Regressionmentioning
confidence: 99%